Comparison of soybean oil and different sources of corn oil on nursery pig growth performance - Jordan, Kyle E.; Goncalves, Marcio Antonio Dornelles; Nemechek, Jeremiah E.; DeJong, Jon A.; Tokach, Michael D.; Goodband, Robert D.; Dritz, Steven S.; DeRouchey, Joel M.; Woodworth, Jason C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2015)
A total of 350 pigs (PIC 1050; initially 26.45 ± 0.09 lb and 45 d of age) were used in a 21-d study to compare the effects of soy oil and 2 sources of corn oil on nursery pig growth performance. The 7 dietary treatments consisted of a corn-soybean meal–based control diet with no added oil or the control diet with 2.5 or 5% soybean oil (NE = 3,422 kcal/lb) or corn oil from 2 different sources (NE = 3,383 kcal/kg for both sources). There were 5 pigs per pen and 10 pens per treatment. Pig weight and feed disappearance were measured on day 0, 7, 14, and 21 of the trial to determine ADG, ADFI, and F/G. Overall (d 0 to 21), increasing corn or soybean oil improved (linear; P < 0.02) ADG, F/G, and final (d-21) BW, but a source × level interaction was observed (P < 0.05) for ADG, F/G, and caloric efficiency (CE; caloric intake/total BW gain). For ADG, increasing soy oil or corn oil source 1 from 2.5 to 5% increased ADG, whereas increasing corn oil source 2 from 2.5 to 5% decreased ADG. Feed efficiency also improved at a greater rate for pigs fed increasing corn oil source 1 compared with the other oil sources. Caloric efficiency was not influenced by soy oil or corn oil source 2 but was improved (linear, P < 0.05) as corn oil source 1 increased in the diet. The improved CE for corn oil source 1 indicated that the energy value of this source was underestimated. In conclusion, soybean or corn oil improved ADG and F/G as expected; however, growth performance varied among the 3 oil sources. This study shows the benefits of adding an oil source in late-phase nursery pig diets to achieve improved ADG, F/G, and CE, but more research is needed to determine the cause of the varied responses between corn oil sources.
Swine Industry Day, 2014 is known as Swine Day, 2014
Keywords: Corn oil; Growth performance; Nursery pig; Soybean oil